2010
DOI: 10.1002/app.33141
|View full text |Cite
|
Sign up to set email alerts
|

SEBS/PPy.DBSA blends: Preparation and evaluation of electromechanical and dynamic mechanical properties

Abstract: In this study, the electromechanical and dynamic mechanical properties of electrically conducting polymer blends were investigated. The blends were comprised poly(styrene-b-butylene-ran-ethylene-b-styrene) (SEBS) containing polypyrrole doped with dodecylbenzenesulfonic acid (PPy.DBSA). The two types of PPy.DBSA (with and without an excess of DBSA) were blended with SEBS through the solution casting method at room temperature. The dynamic mechanical characterization of the SEBS/ PPy.DBSA blends demonstrated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 38 publications
2
19
1
Order By: Relevance
“…From the fitting of the experimental data, f p and t values of 4 wt% and 1.1, respectively, have been found. The percolation threshold observed in this study is quite similar to that reported for the PVDF/PANI.DBSA blend [24], but it is much lower than that observed on SEBS/PANI.DBSA and SEBS/PPy.DBSA blends [9,20]. This behavior is probably induced by the good compatibility between PVDF and PPy components that induces a conducting network formation into PVDF matrix at very low PPy concentration.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…From the fitting of the experimental data, f p and t values of 4 wt% and 1.1, respectively, have been found. The percolation threshold observed in this study is quite similar to that reported for the PVDF/PANI.DBSA blend [24], but it is much lower than that observed on SEBS/PANI.DBSA and SEBS/PPy.DBSA blends [9,20]. This behavior is probably induced by the good compatibility between PVDF and PPy components that induces a conducting network formation into PVDF matrix at very low PPy concentration.…”
Section: Resultsmentioning
confidence: 91%
“…in which c is a constant, t a critical exponent, the resistivity, f the fraction of the conductive medium and f p the fraction at the percolation threshold, expressed as a weight fraction [9,20,27]. From the fitting of the experimental data, f p and t values of 4 wt% and 1.1, respectively, have been found.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…One approach to possibly overcome the above limitations is blending PPy with commercial insulating polymers to produce conductive polymer blends or composites [3,11,27,[29][30][31][32][33]. Among the methods mentioned in the scientific literature, melt mixing offers the advantages of large-scale production and reduced cost which are the bases for any industrial application.…”
Section: Introductionmentioning
confidence: 99%